Consumer Loyalty: Influence of Servicescape, Service Quality, and Lifestyle through Consumer Satisfaction - Revalino Tigor Hasudungan; Jamaludin Khalid; Masrina Gultom (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This research analyses Consumer Loyalty Influenced by Servicecape, Service Quality, and Lifestyle Through Consumer Satisfaction in Koda Bar Jakarta. Methodology: This study involved 92 respondents as samples, with the Accidental Sampling technique used for sampling. We use the Path Analysis method to overcome this problem. This technique allows direct and indirect estimation with the help of the IBM SPSS application. Result: In Stucture 1, Servicescape, Service Quality, and Lifestyle simultaneouly impact Consumer Satisfaction. However, only Service Quality and Lifestyle have a significant partial effect on Consumer Satisfaction, whereas Servicescape does not. In Structure 2, Servicescape, Service Quality, Lifestyle, and Consumer Satisfaction collectively influence Consumer Loyalty. Yet, only Servicescape and Lifestyle significantly affect Consumer Loyalty, while Service Quality and Consumer Satisfaction do not. Additionally, Servicescape, Service Quality, and Lifestyle do not indirectly affect consumer loyalty through consumer satisfaction, as evidenced by the Sobel test results, which show no mediating effect. Conclusion: Service Quality and Lifestyle influence satisfaction, while loyalty is driven by Servicescape and Lifestyle. Satisfaction does not serve as a mediator. These findings highlight the importance of service quality, understanding customer lifestyles, and optimizing the bar’s physical environment. Limitations: This study is limited to one research object only, and has not considered other variables that may also affect consumer loyalty, such as price or promotion. Contribution: This study contributes to the understanding of how factors such as servicescape, service quality, and lifestyle can affect consumer satisfaction and loyalty in the entertainment and hospitality industry, and provides suggestions for entrepreneurs to design better consumer experiences.